Left Atrial Anatomy Relevant to Catheter Ablation - Damián Sánchez-Quintana; José Ramón López-Mínguez; Yolanda Macías; José Angel Cabrera; Farhood Saremi (Cardiology Research and Practice)
The rapid development of interventional procedures for the treatment of arrhythmias in humans, especially the use of catheter ablation techniques, has renewed interest in cardiac anatomy. Although the substrates of atrial fibrillation (AF), its initiation and maintenance, remain to be fully elucidated, catheter ablation in the left atrium (LA) has become a common therapeutic option for patients with this arrhythmia. Using ablation catheters, various isolation lines and focal targets are created, the majority of which are based on gross anatomical, electroanatomical, and myoarchitectual patterns of the left atrial wall. Our aim was therefore to review the gross morphological and architectural features of the LA and their relations to extracardiac structures. The latter have also become relevant because extracardiac complications of AF ablation can occur, due to injuries to the phrenic and vagal plexus nerves, adjacent coronary arteries, or the esophageal wall causing devastating consequences.